UPAYA PENGEMBANGAN OBJEK WISATA DI KOTA PADANG - M. Bayu Pratomo; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Padang has a lot of tourism potential , the potential fine nature, culture , history and others. But very unfortunate that the slow movement of the Department of Culture and Tourism of Padang so that there is untapped potential optimally . Seeing this attraction facilities and infrastructure provided is not adequate , there is still a lack of promotion of tourist attractions , and the lack of cooperation with the private sector . Department of Culture and Tourism of Padang design a program to develop the Region Attractions Padang city into a tourist destination . This study aims to determine the development efforts of attractions in the city of Padang and the factors that influence the development efforts attractions in the city of Padang .The theory used is Yoeti theory that human resources management, transport , service facilities , promotions , and attractions . In this study the author uses descriptive qualitative research methods with research sites in the Department of Culture and Tourism of the city of Padang and who serves as key informant was the head office data collection techniques such as interviews , observation and documentation . And analysis of data from the efforts of development used by the Department of Culture and Tourism and then analyzed what are the factors that influence the development efforts attractions in Padang are supported by interviews conducted by the researchers then be deduced .From the results of this research note that tourism development efforts in Padang made the Department of Culture and Tourism has not yet optimal management of human resources is still need for training , operational transportation does not exist, the need for additional support facilities , attractions along the coast is not optimal . Factors affecting the development efforts of attractions in the city of Padang , namely lack of funds, lack of funds from local government and hampered by land acquisition in the city of Padang .Keyword: Development, Contruction, and Inhibiting Factors